The Expression Of Heat Shock Protein (Hsp) 25 At Compression And Tension Area DuringAlveolar Bone Remodeling - Muhammad Nurul Amin (Universitas Muhammadiyah Yogyakarta, 2012)
The activation of orthodontic appliance will generate mechanical force. This forceis used to depress tooth and the tissues surrounding it then stimulates alveolarbone remodeling. Alveolar bone remodeling is divided into compression andtension area. This stress becomes a signal to activate heat shock responseyielding heat shock protein (HSP) synthesis, especiallyhsp25isessentialforalveolarboneremodelingprocessitself. The aim of this study was to comparehsp25 expression in compression and tension areas. This study using guinea pigsmandibular first insicivus that given a mechanical force to see hsp25 expressionin both areas. The HSP25 expressionwas measured by counting this protein afterbeing conducted by immunohystochemistry method. It is analysed statisticallywith one way Anova with level of significant p = 0,05.